Effects of casting and heat treatment processes on the thermal conductivity of an Al-Si-Cu-Fe-Zn alloy. (February 2017) - Chen, J.K.; Hung, H.Y.; Wang, C.F.; Tang, N.K.
Highlights: Die cast Al alloys bear lower thermal conductivity than gravity cast ones. Pores in die cast Al alloy reduces thermal conductivity. Spheroidized precipitates increase thermal conductivity in Al alloy. Heat treated die casting shows the highest thermal conductivity among all processes. Heat treatment does little to the thermal conductivity of gravity castings. Abstract: In this study, the effects of casting processes and heat treatments on the thermal conductivity of an Al-10 wt% Si-0.6 wt% Cu-0.9 wt% Fe-0.7 wt% Zn aluminum alloy were studied. Both gravity- and die-casting processes were used. The porosity in die castings was controlled by varying the injection pressure and plunger velocity. The porosity, microstructures, and thermal and electrical conductivities of the die castings were characterized. The thermal conductivity of gravity-cast material achieved 143.4 W m −1 K −1, whereas those of die-cast materials ranged from 110.8 to 126.8 W m −1 K −1 . The die-cast aluminum alloys demonstrated considerably finer interconnecting precipitates than did the gravity castings. The closely spaced precipitates acted as barriers for thermal conduction, leading to reduced thermal conductivity. Die-casting pressures and velocities were controlled to form die castings with up to 3.73% porosity, which led to a 12.6% decrease in thermal conductivity. The die-cast Al alloys were then subject to solutionization (T4) and aging treatments (T6). The silicon precipitates were spheroidized, thus widening the paths for heat conduction. The thermal conductivity was greatly enhanced, increasing from 126.8 W m −1 K −1 in the die-cast condition to 151.6 W m −1 K −1 after 550 °C solutionizing and 4 h of aging at 200 °C. The thermal conductivity of the gravity-cast materials remained unchanged after the same heat treatments. Improving the thermal conductivity of die castings through proper heat treatments is crucial for aluminum alloys in rigorous heat-dissipating applications.